An Overview of Cannabis Allergy (Actualité en allergologie et en immunologie au Canada, 2022)
Cannabis refers to a genus of annual, herbaceous, dioecious flowering plants that are members of the family Cannabaceae, which include about 102 plant species.Although there is much debate, the most common taxonomy is that the genus Cannabis comprises one species, Cannabis sativa L (C. sativa)., which includes the highly polymorphic subspecies sativa, and indica. Hemp and cannabis both refer to the same species C. sativa; however, there is important distinction between the two. Whereas hemp (fiber-type) is grown for its cellulose-rich fiber in the stem, cannabis (drug-type) is cultivated for its flowers where the glandular trichomes produce the psychoactive delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD). THC provides the analgesic and relaxing effects of cannabis, whereas CBD produces other effects such as antiemetic and soporific properties. Researchers have used the THC content to define C. sativa subspecies sativa as containing less than 0.3% THC in dried flowering tops of female plants and C. sativa subspecies indicaas containing ≥0.3% THC.This threshold has been used by regulatory bodies to legally differentiate hemp plants (